KORELASI ANTARA GANGGUAN FUNGSI PARU DENGAN UJI JARAK TEMPUH JALAN 6 MENIT Studi pada penderita sekuele tuberkulosis - , Dwi Wirastuti; , dr. Sumardi, SpPD-KP. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
diffuse fibrotic in the lungs, the result is decline pulmonary expansion. Six minute walk test (6MWT) is an example of a simple practical functional test and only requires the ability to walk. This study aims to determine whether there is a correlation between impaired lung function the 6MWT, in tuberculosis sequel study. The study design was post-test only experimental design which conducted in Sardjito hospital and BP4 in Yogyakarta. The subject of this study are 39, 26 men and 13 women. The mean height 1.62 ± 0.08 m, body weight 55 ± 10.65 kg, body mass index was 20.82 ± 3.48 kg / m². Mean FVC and FEV1 was 2.32 ± 0.81 L and 2.06 ± 0.79 L, mean predicted FVC and predicted FEV1 respectively 82.07 ± 20.44 % and 82.1 ± 17,78 % . Median (minimum-maximum) FEV1/FVC was 0.98 (0.48 to 1). The Willcox index 1 were 26 subjects ( 66.7 % ), the Willcox index 2 were 10 subjects (25.6 %) and Willcox index 3 were 3 patients (7.7 %). Six subjects (15.4 %) were restriction, 14 subject were obstruction and 19 subjects were normal. The mean 6 minutes walk distance were 246.3 ± 54.8 meters . Predicted FVC and age were influence six minutes walk distance 33.2%, 66.8% were influenced by other variables, which not examined in this study and there was a significant differences between Willcox index with 6 minutes walk distance in patients with tuberculosis sequelae. TB sequelae subjects which Willcox index 1 will be able to take the six minutes walk distance longer than subject which Willcox index 3.